Impacts of Consumption of Meal on Academic Achievement in Basic Science among Junior Secondary Students in Rivers State - Owo, Wisdom J.; Nwala, Longinus (NIU Journal of Social Sciences, 2019)
This study examined the impact of meal consumption on junior students’ academic achievement in basic science. It is a cross sectional study carried out on 1960 students who enrolled and stayed in their school for at least two years. They were selected from 24 public Junior Secondary Schools in three senatorial districts in Rives State. They responded to a meal time survey scale (MTSS) used to obtain data on the rate of meal intake. Average score of two years Basic Science examination results of the students was taken as the measure for academic achievement. The results were collected from the student’s schools and the average score determined to indicate the achievement level of each of the participants. Percentage, mean and Anova were the statistical tools used in data analysis. Results showed that majority of the students do skip their breakfast and lunch but had their dinner. It also showed that daily eating of breakfast, lunch and dinner significantly (p<.05) promotes academic achievement of students. Thus we recommended that parents should ensure that their children or ward regularly consume breakfast, lunch and dinner on daily basis. Also, government should implement the school free feeding programme. Keywords: Meal consumption, Basic science, Academic achievement, Junior Secondary School.